Spatial Data for Development Domain Analysis in East and Central Africa - International Food Policy Research Institute; Association for Strengthening Agricultural Research in Eastern and Central Africa (International Food Policy Research Institute, 2017)
GIS dataset for constructing three-dimensional Development Domain for ASARECA's operation area in 12 East and Central Africa countries. Data layers of market accessibility, agricultural potential, and population density of 2010 at 5 arc-minute resolution were compiled from HarvestChoice.